Fear Culture in Media: An Examination on Coronavirus Discourse - Chaiuk, Tetyana Andriivna; Dunaievska, Olha Valeriivna (Journal of History Culture and Art Research, 2020)
Fear culture has become a central perspective of viewing life in Western societies where the feeling of vulnerability and insecurity has increased over the past few decades. Sociological studies on the culture of fear provide the theoretical background for understanding how the media coverage of the coronavirus outbreak helps to cultivate the audience’s anxiety. The purpose of this article is to examine how the COVID-19 outbreak was presented in British newspapers and what language means were used to breed the anticipation of danger even before the first lethal case was registered in the UK, that is from January 1 to March 5, 2020. To identify the verbal means employed by newspapers to present the coronavirus as the ultimate threat and thus to cultivate a fear culture among their readers, Critical Discourse Analysis (CDA) is chosen as the main method of the research, since it looks into how language means are used in media texts to produce an intended effect on audiences. The study reveals that the newspapers’ editorials, headings, and articles of that period framed the coronavirus pandemic in terms of fear-mongering by dramatizing reports on the epidemic in China, by metaphorically presenting the coronavirus as deadly living thing approaching Great Britain and finally hitting the country like a tsunami, by repeatedly emphasizing the globality of the pandemic and inadequacy of the government’s measure to curb the disease.